NICHTS NEUES SCHAFFEN (De Gruyter, 2022)
This volume addresses interdependencies between the original and the copy while focusing on the latter. Going beyond established imperatives for innovation, the essays in this volume examine artistic repetition and concentrate on its specific forms, intentions, and contexts. The faithfulness of the copy is thus revealed as a productive category in its own right, even if—or perhaps precisely because—the aim is “creating nothing new.”